The body, masculinities and racisim : social relations between migrant and dominant group boys in three inner city primary schools in Dublin - Garratt, Lindsey (Trinity College (Dublin, Ireland). School of Social Work and Social Policy, 2012)
This thesis explores the interactions and relationships between twenty migrant group boys and thirty-nine dominant group boys in three inner city multi-ethnic primary schools in North Inner City Dublin. Social relations between boys are analysed from a Bourdieusian phenomenology of social space to contend that racism and hegemonic masculine gender identities mutually construct each other through their intersection in the corporeal schema of the habitus. Data from two phases of fieldwork are analysed. The first phase was collected as part of the larger Trinity Immigration Initiative [TII], Children Youth and Community Relations Project [CYCR], 'Learning Together' and consist of fifty-five children, forty-seven boys and eight girls from three class groups [7-8 years old] collected over three periods of three weeks each between January and May 2008. Phase two revisits and re-interviews class group three one year on in May 2009 for the author's PhD study alone. In both phases children were interviewed individually or in dyads according to their preference, thus a total number of forty-two interviews, from fifty-nine participants, fifty-one boys and eight girls, thirty-nine children from the dominant group and twenty from migrant backgrounds are examined in this thesis. Additionally, the data also comprises approximately sixty- five hours of observation notes on the 'child world of the school', space in which the children’s attention was primarily on their peers in the absence of overt adult supervision and control, and twenty-nine hours of in-classroom observation from the wider CYCR project.
Keywords: Social Studies, Ph.D.; Ph.D. Trinity College Dublin